Modelagem unidimensional de dados do método MCSEM com variação na resistividade da água do mar e na orientação dos sensores - LUZ, Edelson da Cruz (Universidade Federal do Pará, 2014)
The Marine Controlled Source ElectroMagnetic (MCSEM) is a new geophysical method that is very promising in the detection of resistive layers in the sediments under the oceanic floor, a useful information for the oil industry. In this work we model MCSEM data including variations in the resistivity of the ocean water. Such variations can arise from the influence of marine currents, temperature gradients or any other source of influence on the water salinity. We observe that the data from this method are significantly affected by those variations.We also simulate the random positioning of the receivers when deployed to the sea botton, our results show a strong decline in the amplitude of the signal when the receivers are located at a certain distance from the ideal array line.